Data visualization for agricultural data: benefits and challenges - Sidi, Fatimah; Ishak, Iskandar; Affendey, Lilly Suriani (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
Data visualization is an important field in the Big Data domain. Its purpose is to provide meaningful visual interpretation of data that comes from various resources for enabling users to interpret and understand the data. In agricultural research, data visualization is very important to enhance the discovery of information and to make sense of large amount of data that is complex in nature. This paper reviews the approaches that have been implemented in visualizing agricultural data. This paper also highlights the benefits as well as challenges and discusses future direction of the implementation of data visualization for agricultural data.